THE MEANING OF ADVERTISING 'AQUA LIFE' IN THE SEMIOTIC PERSPECTIVE OF ROLAND BARTHES - ASIMA OKTAVIA SITANGGANG (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2020)
The purpose of this study was to determine the meaning of AQUA LIFE #Bijak Plastics advertising. The ad is trying to move consumers to campaign about reducing plastic waste, by using 100% recycled plastic. By using Roland Barthes's semiotic analysis method, the writer found several meaning constructions of AQUA LIFE #BijakBerplastik with 60 seconds duration. This ad not only invites consumers to contribute to continuing the good for the earth by reducing plastic waste but also reinforces the construction of its branding strategy which is reflected in two main myths: (1) Aqua's consistency in providing services and building customer loyalty; (2) Aqua's brand personality that is pure, committed and cares for the environment.